Crystal chemistry of halurgite, Mg4[B8O13(OH)2]2·7H2O, a microporous heterophylloborate mineral. (31st May 2019) - Pekov, Igor V.; Zubkova, Natalia V.; Ksenofontov, Dmitry A.; Chukanov, Nikita V.; Korotchenkova, Oksana V.; Chaikovskiy, Ilya I.; Yapaskurt, Vasiliy O.; Britvin, Sergey N.; Pushcharovsky, Dmitry Yu.
Abstract: Three samples of halurgite were re-examined: two from the Chelkar salt dome in the North Caspian Region, Western Kazakhstan (the type locality and including the type specimen), and one from a new locality in the Satimola salt dome located in the same region. The crystal structure of halurgite has been solved for the first time on the specimen from Chelkar with the empirical formula Mg3.94 [B8.03 O13.03 (OH)1.97 ]2 ·7.16H2 O; refinement began with single-crystal X-ray diffraction data and was subsequently refined on a powder sample using the Rietveld method ( R p = 0.0232, R w p = 0.0354 and R obs = 0.0558). The idealised crystal chemical formula of halurgite is Mg4 [B8 O13 (OH)2 ]2 ·7H2 O. The mineral is monoclinic, P 2/ c, a = 13.201(2), b = 7.5622(10), c = 13.185(2) Å, β = 91.834(14)°, V = 1315.6(4) Å 3 and Z = 2. The crystal structure is unique. Eight B polyhedra form a fundamental building block [B8 O16 (OH)2 ], which is a six-membered borate ring (built by two pairs of B tetrahedra and two B triangles) with two additional triangular BO2 (OH) groups. Each [B8 O16 (OH)2 ] ring is linked to six adjacent analogous rings to form a [B8 O13 (OH)2 ]∞ layer. These layers are connected via MgO6 and Mg(OH)2 (H2 O)4 octahedra into a microporous heteropolyhedral pseudo-framework. The crystal structure of halurgite can also be described in terms of an approach developed for heterophyllosilicates containing three-layer HOH modules, where HOH refers to an octahedral layer O sandwiched between two heteropolyhedral layers H . In halurgite the HOH module consists of two heteropolyhedral (BO3 triangles + BO4 tetrahedra) borate H layers [B8 O13 (OH)2 ]∞ and a central interrupted O layer composed of MgO6 octahedra, whereas a more voluminous Mg(OH)2 (H2 O)4 octahedral complex and additional H2 O molecules are located between HOH modules. Halurgite and four related synthetic H-free borates M 2 Cd3 B16 O28 and M 2 Ca3 B16 O28 ( M = Rb or Cs) can be considered microporous heterophylloborates.